Improve the Maha Sarakham clay properties by grog addition - Punsukmtana, Lada; Pharaboon, Sasithorn; Kitchainukul, Danai (Bulletin of Applied Sciences, 2015)
The study aims of an improved the Maha Sarakham clay property by grog addition was to understand the effect of grog on properties of a body for Ban Moh (Pottery village), Muang district, Maha Sarakham province, Thailand. Grog was prepared by the mud from Nong loeng, Tumbom Kewa, Maha Sarakham province, and the rice husk. It was fired, grinded, and sifted through a 60 mesh sieve. The grog was mixed with the clay from the same source. The ratios of clay:grog to prepare a body were 80:20 70:30 60:40 50:50. The body was aged, kneaded, formed, and fired at 700-1200°C. The body physical properties were measured before and after fired: shrinkage, water absorption, density, and modulus of rupture. The phase, thermal property, and microstructure were also studied. The experimental results showed that an increase in grog in the body increased the body open porosity and leaded to increase in the water absorption and reduce in the drying shrinkage, firing shrinkage and density. The sample fired at low temperature, 800°C, appeared to be porous and gained Quartz as the major phase with low modulus of rupture and low thermal expansion. An increase in the firing temperature to 1200°C reduced the porosity, water absorption, but increased the firing shrinkage and density. The major phases as Cristobalite and Mullite caused an increase in the thermal expansion and the modulus of rupture consecutively. This study showed the chance of improving the Maha Sarakham clay properties by grog addition.